The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/aocs.12589
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting pure component wax esters as basis of wax‐based oleogels

Abstract: Current research on wax‐based oleogels indicates wax esters to be the key component in many natural waxes. This necessitates understanding the properties of pure wax esters to unravel the gelling mechanism in wax‐based oleogels. Therefore, available literature data on pure wax esters is summarized and critically reviewed. The detailed analysis of the pre‐existing data on crystallographic (SAXS) and thermal properties, facilitates the interpretation of subsequently performed experiments: Specific wax esters wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
4
16
0
Order By: Relevance
“…The platelet-based cardhouse networks are often interpreted to be needle-based. This misinterpretation of light–microscopic images was previously pointed out by Hwang et al in 2015 [ 23 ] and repeatedly confirmed, e.g., [ 9 , 18 , 24 ].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…The platelet-based cardhouse networks are often interpreted to be needle-based. This misinterpretation of light–microscopic images was previously pointed out by Hwang et al in 2015 [ 23 ] and repeatedly confirmed, e.g., [ 9 , 18 , 24 ].…”
Section: Introductionsupporting
confidence: 64%
“…The axes for these properties were normalized such that the single FA occurring between a CN of 14 and 24 and a single FaOH with a CN between 16 and 32 could be depicted. The mean CN of the WE fraction was calculated assuming a statistical recombination of the respective FA and FaOH moieties, as previously described [ 9 ]. In line with the other parameters, the axis for the mean CN of the WE fraction was from the shortest CN present (CN = 30) to the longest CN present (CN = 56).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wax esters are the main components in SFW (96–100%) and RBX (92–97%), while this amount for BW and CDW were significantly lower (58–71%) and (16–35%), respectively, that shows the diversity of different components in these waxes ( Blake et al (2014) . In a recently published paper, Brykczynski et al (2022) showed a significant increase in G* in binary wax esters (1:1 w/w ratio) containing similar total carbon number wax esters, suggesting some sort of “compound” formation, or synergistic interaction at the molecular level. Previous studies showed the total carbon number for RBW and SFW were (44–64) and (36–54), respectively ( Blake et al (2014) ).…”
Section: Resultsmentioning
confidence: 91%